Development of Equations Relates the Factors Affecting Riverbank Stability Using Dimensional Analysis. Issue 1 (February 2021) - Aldefae, Asad H.; Alkhafaji, Rusul A.
Abstract: Many previous studies had been investigated the riverbank stability since of its great significance in prohibition flood risk that may command many economic and environmental problems. Investigating the riverbank stability due to development of cracks that represents the main causes of failure is very important, to prepossess recurring landslides by characterizing the riskiest areas and remediating them using a suitable method. In this paper, Dimensional analysis (DA)was carried out to formulate reasonable hypotheses about the complex physical conditions related to riverbank stability investigation. Two empirical equations were derived; the first one for the rate of settlement in riverbank soil, and the other for the failure angle of the slope. Depending on the experimental results that were applied in the software of IBM SPSS Statistics, v24, both equations gave good compatibility where the correlations coefficients were 0.9877 and 0.9826 respectively.